Relevansi Maqasid Syariah dalam Menyikapi Fenomena Nikah Sirri di Masyarakat Indonesia - M. Kiman, M. Kiman (Jurnal El-Thawalib, 2025)
Sirri marriage raises pros and cons in various circles: from the 'ulama, legal practitioners to community leaders. This difference of opinion is due to differences in perception. The 'ulama consider the legality in Shari'ah terms, legal practitioners are guided by the Compilation of Islamic Law, while community leaders look more at social order. This paper examines Sirri's marriage law from the perspective of Maqashid Sharia by considering between maslahat and mafsadat in the study of Islamic legal philosophy.